2010
DOI: 10.1002/prep.200900110
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Performances of Castable HTPB/CL‐20 Booster Explosives

Abstract: HTPB/CL‐20 castable booster explosives were prepared successfully by a cast‐cured process. Scanning electron microscope (SEM) and the charge density test were employed to characterize the molding effect of HTPB/CL‐20 explosives. The propagation reliability, detonation velocity, mechanical sensitivity, thermal decomposition characteristics and thermal stability of the HTPB/CL‐20 explosives were also measured and analyzed. The results show that, when CL‐20 content is less than 91 wt.‐%, the charges with better m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…The effects of CL-20 and RDX on basic properties of CMDB propellants were investigated, the major findings could be summarized as follows: 1) The calculations on energetic properties for CL-20/RDX-CMDB propellants showed that energetic properties of propellant with CL-20 were superior to of propellant with RDX. 2) The data on burning rate revealed that with the increase of RDX/CL-20 mass fraction in the propellants, the burning rates at low pressure (2-8 MPa) remained almost the same but differ observably at high pressure (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). With the increase of CL-20 mass fraction in the propellants, the burning rates of propellants could be enhanced significantly, but the burning rates of propellants containing RDX decreased.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The effects of CL-20 and RDX on basic properties of CMDB propellants were investigated, the major findings could be summarized as follows: 1) The calculations on energetic properties for CL-20/RDX-CMDB propellants showed that energetic properties of propellant with CL-20 were superior to of propellant with RDX. 2) The data on burning rate revealed that with the increase of RDX/CL-20 mass fraction in the propellants, the burning rates at low pressure (2-8 MPa) remained almost the same but differ observably at high pressure (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). With the increase of CL-20 mass fraction in the propellants, the burning rates of propellants could be enhanced significantly, but the burning rates of propellants containing RDX decreased.…”
Section: Resultsmentioning
confidence: 97%
“…Joseph Kalman et al [17] investigated the effect of CL-20 particle size on the combustion of CL-20/HTPB propellants down to submicrometer sizes, the burning rate and combustion mechanism were discussed in detail. A large number of papers have been concerned with the combustion and energetic properties of HTPB and NEPE propellants [18][19][20][21][22][23][24]. However, there are very few publications on the effect of CL-20 particles on the combustion and energetic properties of composite modified double-base propellants (CMDB) [25][26][27], especially on its combustion residues properties.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, polymers like thermoplastic elastomers (TPEs), such as copolymers of ethylene and vinyl acetate [ethylene vinyl acetate (EVA) copolymers] and Estane have found application as binders in sheet explosive formulations [3,4]. Among the polymers, low molecular weight liquid poly-butadienes with terminal functional groups, like hydroxyl terminated polybutadiene (HTPB), have found wide application in the area of propellants and PBXs [5,6]. HTPB is a preferred choice due to its clean curing reactions, stable urethane linkages formed by isocyanate curing, and superior fuel content.…”
Section: Introductionmentioning
confidence: 99%
“…
Abstract:The present investigation reports the use of 2, 4,6,8,10,4,6,8,10, in sheet explosive formulations. In this study, hydroxyl terminated polybutadiene (HTPB) based sheet explosives were prepared incorporating the powerful explosive CL-20 as a partial replacement for hexahydro-1,3,5-trinitro-1,3,5-triazine(RDX).
…”
mentioning
confidence: 99%
“…PBXs possess good safety performance, high mechanical strength and ease of molding and other significant advantages through making full use of the high energy output of the HEDC [4] and the excellent plasticity of polymer materials. XTX-8003, XTX-8004 and HTPB/CL-20 booster explosives [5][6][7] are three kinds of typical PBXs used in logic explosive circuits, which use pentaerythritol tetranitrate (PETN), 1,3,5-trinitroperhydro-1,3,5-triazine (RDX) and ε-2,4,6,8,10,12-hexanitro-2,4,6,8,10,12-hexaazaisowurtzitane (CL-20) as HEDCs. They all meet the specific requirements of explosive circuits when combined with the polymer materials.…”
Section: Introductionmentioning
confidence: 99%